The Influence of the Arabic Language on the Dari Persian Language - Abdul Khaliq Musaddiq (RIRAI Publisher, 2023)
Despite the fact that the Arabic and Persian languages ​​are derived from two different origins, they have had a very close interaction throughout the historical periods due to the continuous communication between the two Iranian and Arab peoples, and in this way, the influence of the two languages ​​has created works. Has left from each one to the other, which may not be seen in any other two languages. Unlike civilizations such as Egyptian civilization, which forgot its previous language in front of Arabic and Islamic civilization, Iranian civilization and Persian language, while accepting the Arabic language, did not give up at once and established a two-way interaction with it from the very beginning. These two languages ​​have borrowed many words from each other. In Persian, most jurisprudential, religious and legal terms are taken from Arabic. But the Arabic language, in its turn, has borrowed some words from Persian in an intact form and a lot of words in a confused form (in the form of Arabic forms). This article aims to examine the influence of Arabic language on Persian and to point out some of its aspects. Nevertheless, in most researches and studies, the most recognition or exaggeration has been on the side of the influence of Arabic language on Persian, and this article examines the real limits of this two-way influence.